2015
DOI: 10.1161/hypertensionaha.115.05319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Blood Pressure and Cardiovascular Risk Factors

Abstract: A part from skeletal diseases, vitamin D deficiency is considered a risk factor for cardiovascular events and mortality. [1][2][3][4][5][6] Nevertheless, it remains unclear whether low 25-hydroxyvitamin D (25[OH]D) concentrations are a significant causal risk factor or are simply related to adverse outcomes because of reverse causation and confounding factors, such as obesity, reduced mobility with low sunlight exposure, poor nutrition, or inflammation. [1][2][3][4][5][6] Because high blood pressure (BP) has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 42 publications
12
163
4
5
Order By: Relevance
“…A recent meta-analysis on a large number of studies found no evidence of vitamin D supplementation on BP reduction (40). Also, two recent RCT in hypertensive patients with low 25(OH)D 3 levels did not find a significant effect of vitamin D supplementation on BP (24,365). Together, these findings do not support the use of vitamin D as treatment for hypertension.…”
Section: Iii) Randomized Control Trialsmentioning
confidence: 82%
“…A recent meta-analysis on a large number of studies found no evidence of vitamin D supplementation on BP reduction (40). Also, two recent RCT in hypertensive patients with low 25(OH)D 3 levels did not find a significant effect of vitamin D supplementation on BP (24,365). Together, these findings do not support the use of vitamin D as treatment for hypertension.…”
Section: Iii) Randomized Control Trialsmentioning
confidence: 82%
“…27 These results were confirmed by another recent trial that found that cholecalciferol supplementation had no effect on 24-hour systolic blood pressure in hypertensive patients with low 25-hydroxyvitamin D levels. 28 Our study has some limitations that must be noted. First, the observational design limits inferring causality from these results.…”
Section: Discussionmentioning
confidence: 90%
“…Major finding of the study was that low levels of 25-hydroxy vitamin D and 1,25-dihydroxyvitamin D were associated with prevalent myocardial dysfunction, deaths due to heart failure, and SCD [15].…”
Section: Heart Diseasementioning
confidence: 98%
“…Suppression of the cardiac Renin-Angiotensin System (RAS) and of natriuretic peptides may partially mediate these antihypertrophic effects of vitamin D. Apart from this; vitamin D exerts various effects on the growth and differentiation of cardiomyocytes. One beneficial key mechanism of vitamin D is to inhibit excessive proliferation of cardiomyocytes [15].…”
Section: Heart Diseasementioning
confidence: 99%